Comparison of Dietary Supplements Consumption Between Female University and National Team Sports Athletes in Malaysia. (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2022)
Dietary supplement consumption had already become well known among athletes especially those who were involved in team sports to enhance performances, health benefits, and nutritional strategies. This study aimed to determine the difference in dietary supplement consumption between the female university and national team sports athletes in Malaysia. The Dietary Supplement Questionnaire was used to compare the participants’ dietary supplements usage and it was distributed online via a Google Form. Results from this study showed there was no significant difference in the usage of individual vitamins/minerals. However, based on frequency, the usage of vitamin C was the most popular among these groups. Next, there was a significant difference in the usage of protein powder (t = -2.435, df = 61, p <0.018) and, creatine (t = -2.192, df = 61, p <0.032) between the female university and national athletes. After that, there was a significant difference in usage of other supplements and sports aid which was fish oil/omega 3 (t = -1.466, df = 61, p < 0.032). The national athletes showed higher consumption of dietary supplements compared to the university athletes due to their higher level of competition, energy requirement, and long-time of training.